Analysis of Nagari Development Based on Natural Resource Potential in IV Koto Aur Malintang District, Padang Pariaman Regency - Wita Puspa Dewita; Yurni Suasti (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
This study aims to analyze the level of nagari development based on natural resource potential in IV Koto Aur Malintang District, Padang Pariaman Regency. A descriptive quantitative approach was employed, with all nagari in the district selected as research samples using a saturated sampling technique. The study focuses on natural resource–based development, particularly in the agricultural and plantation sectors, referring to the indicators outlined in Ministry of Home Affairs Regulation No. 12 of 2007. Data were obtained from secondary sources, including official nagari government documents, and supported by primary data collected through field observations. Data analysis was conducted using descriptive quantitative techniques through ordinal scale scoring to classify nagari development levels. The results indicate variations in development levels among nagari, influenced by differences in land ownership, plantation area, agricultural productivity, and resource utilization. Nagari with larger productive land areas and higher production levels tend to exhibit better development performance. However, the dominance of intermediary-based marketing systems limits the added value received by local communities. These findings suggest that natural resources play a crucial role in nagari development, but their effectiveness depends on optimal management, institutional strengthening, and sustainable utilization.